Analisis Kesiapan Pemerintah Kabupaten Banyumas dalam Pelaksanaan Perda Nomor 4 Tahun 2012 Tentang Rencana Induk Pengembangan E-Government di Kabupaten Banyumas - Perdani, Titis; ., Kushandayani; Herawati, Nunik Retno (Journal of Politic and Government Studies, 2015)
In 2012,the government of BanyumasRegency authorized Local Regulation No. 4 of2012 on the Master Plan for Development of E-government in Banyumas Regency.BanyumasRegency becomes the only regency in Central Java which has regulation regarding Egovernmnetand received many awards in the field of IT. For that reason, this research aims tosee what and how the action plan will be implemented over the next 5 years and how thereadiness of the government of Banyumas Regency. The method used in this paper is descriptivequalitative method. The data source obtained from the primary data, which is through interviewswith informants or key person by snowball sampling technique.Meanwhile, secondary dataderived from the data of documents, archives, and other sources related to the research.Analysistechniques used in this research is qualitative data analysis in the form of description, illustration,and drawing conclusions on the tendencyresearched.Keywords: Readiness, Regency Government, Implementation of Local Regulation, EGovernment.